Healthcare Data Migration: A Technical Framework for Digital Transformation Success - Suhas Lakum (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article analysis explores the critical aspects of healthcare data migration within the context of digital transformation. The article examines the challenges, technologies, and implementation frameworks that healthcare organizations face during migration initiatives. It addresses the complexities of managing diverse medical data types, regulatory compliance requirements, and technical infrastructure needs while maintaining continuous patient care operations. The article investigates enterprise solutions, including VMware vMotion and Dell EMC PowerPath, alongside cloud-native approaches for optimizing migration processes. Through extensive case studies and real-world applications, the article demonstrates the significance of structured planning, quality assurance protocols, and resource allocation in successful migration projects. Furthermore, it evaluates the financial implications and return on investment of migration initiatives while considering future technological trends and strategic recommendations for healthcare organizations undertaking digital transformation journeys. The findings emphasize the importance of a balanced approach between technological advancement and maintaining healthcare service quality throughout the migration process.